2002
DOI: 10.1242/jcs.00034
|View full text |Cite
|
Sign up to set email alerts
|

Diverting intracellular trafficking ofSalmonellato the lysosome through activation of the late endocytic Rab7 by intracellular delivery of muramyl dipeptide

Abstract: Previously, we showed that live Salmonella-containing phagosomes(LSP) recruit early acting Rab5 and promote fusion with early endosomes, thus avoiding transport to the lysosomes. Therefore, live Salmonellasurvive in a specialized compartment. Here we show that scavenger-receptor-mediated intracellular delivery of muramyl dipeptide (MDP)to macrophages leads to efficient killing of Salmonella both in vitro and in vivo. To understand the intracellular trafficking modulation of Salmonella by delivery of MDP, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…Based on the present data, it can be proposed that an opposite effect would be seen with these drugs with respect to vertical transmission of HIV-1. In contrast, our data raise the interesting possibility that altering the endocytic Rab content by intervention in appropriate signal transduction events may offer a new strategy for modulating the targeting of HIV-1 to a degradative compartment (69). Additional studies are needed to define the validity of this approach.…”
Section: Discussionmentioning
confidence: 85%
“…Based on the present data, it can be proposed that an opposite effect would be seen with these drugs with respect to vertical transmission of HIV-1. In contrast, our data raise the interesting possibility that altering the endocytic Rab content by intervention in appropriate signal transduction events may offer a new strategy for modulating the targeting of HIV-1 to a degradative compartment (69). Additional studies are needed to define the validity of this approach.…”
Section: Discussionmentioning
confidence: 85%
“…This late stage in SCV maturation is not fully understood, yet. On the one hand, studies using primary macrophages demonstrated that SCVs do fuse with the lysosomal compartment (Mills and Finlay, 1998;Garvis et al, 2001;Mukherjee et al, 2002). On the other hand, however, studies indicated that despite expressing the phagosomal marker LAMP1, SCVs do segregate and avoid fusion with mature lysosomes to establish a replicative niche for the Salmonella.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic bacteria have developed two major strategies to counteract macrophage killing after phagocytosis, either by escaping from the endocytic vacuoles and inducing cell death (14,25,50) or by resisting the antimicrobial environment of the phagolysosome (32,41,43). We previously reported that the reference AIEC strain LF82 did not induce the death of infected macrophages despite the high replication of bacteria observed within large vacuoles (19).…”
Section: Discussionmentioning
confidence: 99%